A Second-Order Confirmatory Factor Analysis of the Moral Distress Scale-Revised for Nurses - Sharif Nia, Hamid (Nursing ethics, 2019)
Background:Moral distress is a growing problem for healthcare professionals that may lead to dissatisfaction, resignation, or occupational burnout if left unattended, and nurses experience different levels of this phenomenon.Objectives:This study aims to investigate the factor structure of the Persian version of the Moral Distress Scale–Revised in intensive care and general nurses.Research design:This methodological research was conducted with 771 nurses from eight hospitals in the Mazandaran Province of Iran in 2017. Participants completed the Moral Distress Scale–Revised, data collected, and factor structure assessed using the construct, convergent, and divergent validity methods. The reliability of the scale was assessed using internal consistency (Cronbach’s alpha, Theta, and McDonald’s omega coefficients) and construct reliability.Ethical considerations:This study was approved by the Ethics Committee of Mazandaran University of Medical Sciences.Findings:The exploratory factor analysis (N = 380) showed that the Moral Distress Scale–Revised has five factors: lack of professional competence at work, ignoring ethical issues and patient conditions, futile care, carrying out the physician’s orders without question and unsafe care, and providing care under personal and organizational pressures, which explained 56.62% of the overall variance. The confirmatory factor analysis (N = 391) supported the five-factor solution and the second-order latent factor model. The first-order model did not show a favorable convergent and divergent validity. Ultimately, the Moral Distress Scale–Revised was found to have a favorable internal consistency and construct reliability.Discussion and conclusion:The Moral Distress Scale–Revised was found to be a multidimensional construct. The data obtained confirmed the hypothesis of the factor structure model with a latent second-order variable. Since the convergent and divergent validity of the scale were not confirmed in this study, further assessment is necessary in future studies.